1990
DOI: 10.1002/ptr.2650040507
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic effect of Opuntia ficus indica in non insulin‐dependent diabetes mellitus patients

Abstract: Opuntia ficus indica exerts hypoglycemic effects in NIDDM patients independent of its heating or blending during preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 3 publications
0
54
0
2
Order By: Relevance
“…The cladodes are utilized, in traditional medicine, for the management of ulcers, wounds, rheumatic pain and fatigue. Experimental studies showed that cactus pear could reduce glucose and cholesterol levels in human blood (Frati et al, 1990;Stintzing et al, 2001). Chemopreventive effect on oxidative stress and genotoxicity was also recently investigated (Brahmi et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…The cladodes are utilized, in traditional medicine, for the management of ulcers, wounds, rheumatic pain and fatigue. Experimental studies showed that cactus pear could reduce glucose and cholesterol levels in human blood (Frati et al, 1990;Stintzing et al, 2001). Chemopreventive effect on oxidative stress and genotoxicity was also recently investigated (Brahmi et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…248) is an attractive crop in this application because its dark purple fruit have medicinal benefits, and this accession tolerates drought, salt, and B while accumulating and volatilizing Se (Bañ uelos and Lin, 2010). Without Se enrichment, Opuntia fruit and cladode already contain chemotherapeutic qualities that, when eaten, have been shown to help protect the human immune and nervous systems, prevent oxidative stress, help treat gastritis, hyperglycemia, arteriosclerosis, diabetes, and prostatic hypertrophy, and help prevent multiple human cancers (Frati et al, 1990;Hegwood, 1990;Palevitch et al, 1993;Dok-Go et al, 2003;Kuti, 2004;Zou et al, 2005;Feugang et al, 2006). Opuntia fruit is also considered an excellent source of mineral nutrition, being enriched in calcium, potassium, and magnesium (Feugang et al, 2006).…”
mentioning
confidence: 99%
“…cladodes are used for the treatment of gastric ulcer (Galati et al, 2001). Pre-treatment test in rats revealed a protective action against ethanol-induced ulcer (Galati et al, 2003).…”
Section: Anti-ulcer Activitymentioning
confidence: 99%
“…It has been used in traditional folk medicine because of its role in treating a number of diseases and conditions, including antiinflammatory effects (Park et al, 1998), hypoglycemic effects (Frati et al, 1990), inhibition of stomach ulceration (Galati et al, 2003), neuroprotective effects (Dok-Go et al, 2003). Through antioxidant actions and also used for treating diabetes, burns, bronchial, asthma and indigestion in many countries over the world (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%